Nothochrysinae (Neuroptera: Chrysopidae): New Larval Description and Generic Synonymy, with a Consideration of Generic Relationships - Catherine A. Tauber (Psyche: A Journal of Entomology)
Semaphorant B of Kimochrysa africana (Kimmins) expresses all of the larval synapomorphies that characterize the subfamily Nothochrysinae. Except for its head markings, the larva appears identical to that of Hypochrysa elegans (Burmeister). Based on consideration of both larval and adult similarities, Kimochrysa (Tjeder) is designated to be a subjective synonym of Hypochrysa Hagen (New Synonymy). The morphological basis for a previously proposed generic subdivision of Nothochrysinae is evaluated; the results indicate that the subfamily can be organized into two generic groupings each with distinct suites of shared adult characters. As yet, apomorphic support is not forthcoming from adult characters, and, unfortunately, larvae are known from only a few genera in the subfamily.